Potassium supply reduces cesium uptake in Konara oak not by an alteration of uptake mechanism, but by the uptake competition between the ions. (November 2019) - Kobayashi, Riona; Kobayashi, Natsuko I.; Tanoi, Keitaro; Masumori, Masaya; Tange, Takeshi
Abstract: Radiocesium contamination of forests has been a severe problem after the Fukushima Daiichi Nuclear Power Plant accident in 2011. Bed logs of Konara oak ( Quercus serrata Murray), used for mushroom cultivation, were an economically important product from the forests prior to their contamination. One of the potential countermeasures to reduce radiocesium content in trees is potassium fertilization, but the evidence for the effect of K + in reducing Cs + uptake has not been obtained yet in the woody plant. Therefore, we investigated the ability of rhizospheric K + to suppress uptake and translocation of Cs + in Konara oak seedlings through hydroponic experiments in order to clarify the effect of K + . Elemental analysis showed that the seedlings cultivated for 4 weeks under low-K (K + = 50 μM) contained higher amount of Cs comparing to the seedlings cultivated under high-K (K + = 3 mM). Then, the uptake rate of Cs + and K + in the seedlings from the solution having 50 μM K + and 0.1 μM Cs + was calculated using radioactive 137 Cs + and 42 K + to evaluate the effect of growth condition on the ion uptake mechanism. The interference between Cs + and K + at the site of root uptake was also evaluated based on the Cs + and K + uptake rates at K + concentrations of 50 μM, 200 μM, and 3 mM in the seedlings grown under the medium-K (K + = 200 μM) condition. As a result, the Cs + uptake rate at 50 μM K + was not influenced by the growth condition, whereas Cs + uptake decreased when the uptake solution itself was supplemented with 3 mM K + . In addition, the Cs/K ratio in the seedlings was found to rise to exceed the Cs/K ratio in the culture solution as the rhizospheric K + concentration increased, which was in contrast with previous findings in herbaceous plants. Our experiments demonstrated the first direct evidence for woody plants that a high K + concentration can suppress Cs accumulation in Konara oak and that it was derived from competition for uptake between K + and Cs + in the rhizosphere, not from the growth K + condition. Highlights: The effect of K + to suppress Cs + uptake can be applicable to woody plant Konara oak. Cultivation of seedlings under K + sufficient condition does not lower uptake rate of K + nor Cs + . Uptake competition between K + and Cs + is a major factor to suppress Cs + uptake. Ratio of Cs/K in seedlings exceeds the ratio in culture solution if K + is sufficient.